Student perceptions of the socialization and implementation Merdeka Belajar Kampus Merdeka program - Tridelvy Sensony; Dadang Sukirman; Ahmad Fajar Fadlillah (Universitas Pendidikan Indonesia, 2024)
This study analyzes the perceptions of students of the Universitas Pendidikan Indonesia about the implementation of the Merdeka Belajar Kampus Merdeka Program Policy, including their interests and expectations related to learning activities. The background of this study focuses on the importance of socialization programs in improving student understanding and participation. The method used in this research is a quantitative approach with a descriptive design involving 40 respondents who are active students and have finished the program for at least one semester. Data were collected using a closed questionnaire with 30 statements with a Likert scale and then analyzed using descriptive analysis. The findings revealed that students' perceptions of program socialization and independent study implementation were rated to be in the category of